+0  
 
+1
32
1
avatar

The table shows values for functions  f(x) and  g(x)

What is the solution to  f(x)=g(x)

Select each correct answer 

x = -3

x = -2

x = -1

x = 0

x = 1

x = 2

x = 3

 

The functions   f(x)=−2x+2 and   g(x)=(1/3)x+1 are shown in the graph.

What are the solutions to  −2x+2=(1/3)x+1?

Select each correct answer 

-1

0

2

3

4

 
Guest Jan 9, 2018

Best Answer 

 #1
avatar+5888 
+1

1.

 

When   x = -2 ,   f(x) = 4   and   g(x) = 4   so when   x = -2 ,   f(x) = g(x) .

 

When   x = -1 ,   f(x) = 2   and   g(x) = 2   so when   x = -1 ,   f(x) = g(x) .

 

None of the other values for  x  make  f(x) = g(x) .

 

 

2.

 

The solutions to   -2x + 2  =  (1/3)x + 1   are the solutions to  f(x) = g(x) .

 

When   x = -1 ,   f(x) = 4   and   g(x) = 4   so when   x = -1 ,   f(x) = g(x) .

 

When   x = 0 ,   f(x) = 2   and   g(x) = 2   so when   x = 0 ,   f(x) = g(x) .

 

None of the other values for  x  make  f(x) = g(x) .

 
hectictar  Jan 9, 2018
Sort: 

1+0 Answers

 #1
avatar+5888 
+1
Best Answer

1.

 

When   x = -2 ,   f(x) = 4   and   g(x) = 4   so when   x = -2 ,   f(x) = g(x) .

 

When   x = -1 ,   f(x) = 2   and   g(x) = 2   so when   x = -1 ,   f(x) = g(x) .

 

None of the other values for  x  make  f(x) = g(x) .

 

 

2.

 

The solutions to   -2x + 2  =  (1/3)x + 1   are the solutions to  f(x) = g(x) .

 

When   x = -1 ,   f(x) = 4   and   g(x) = 4   so when   x = -1 ,   f(x) = g(x) .

 

When   x = 0 ,   f(x) = 2   and   g(x) = 2   so when   x = 0 ,   f(x) = g(x) .

 

None of the other values for  x  make  f(x) = g(x) .

 
hectictar  Jan 9, 2018

10 Online Users

avatar
avatar
We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details